Pectoralis Major Muscle Belly Rupture in a 17-Year-Old Female Softball Player: A Case Report. Issue 1 (16th January 2023) - Kuechly, Henry A; Figueras, Jorge H; Figueras, Jorge; Gordon, Garrett; Johnson, Brian M; West, Justin W; Grawe, Brian M
Abstract : Case: We report the case of a healthy 17-year-old female softball player with a subacute full-thickness intramuscular tear of the pectoralis major (PM) muscle. A successful muscle repair was obtained using a modified Kessler technique. Conclusions: Despite initially being a rare injury pattern, the incidence of PM muscle rupture is likely to increase as interest in sports and weight training increases, and although this injury pattern is more common in men, it is becoming more common in women as well. Furthermore, this case presentation provides support for operative treatment of intramuscular ruptures of the PM muscle.